2014
DOI: 10.1016/j.ccr.2014.01.010
|View full text |Cite|
|
Sign up to set email alerts
|

A Peptide Mimicking VGLL4 Function Acts as a YAP Antagonist Therapy against Gastric Cancer

Abstract: The Hippo pathway has been implicated in suppressing tissue overgrowth and tumor formation by restricting the oncogenic activity of YAP. However, transcriptional regulators that inhibit YAP activity have not been well studied. Here, we uncover clinical importance for VGLL4 in gastric cancer suppression and find that VGLL4 directly competes with YAP for binding TEADs. Importantly, VGLL4's tandem Tondu domains are not only essential but also sufficient for its inhibitory activity toward YAP. A peptide mimicking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
530
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(546 citation statements)
references
References 57 publications
(67 reference statements)
15
530
1
Order By: Relevance
“…In contrast, expression of Yap is elevated in GC samples compared with matched noncancerous samples as previously described. 33 Furthermore, Yap is a confirmed predictor of poor prognosis in a variety of cancers 34 including gastric cancer. 33 Moreover, the IHC image demonstrated a significant elevated nuclear location of Yap in GC tissues compared with noncancerous tissues, consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, expression of Yap is elevated in GC samples compared with matched noncancerous samples as previously described. 33 Furthermore, Yap is a confirmed predictor of poor prognosis in a variety of cancers 34 including gastric cancer. 33 Moreover, the IHC image demonstrated a significant elevated nuclear location of Yap in GC tissues compared with noncancerous tissues, consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, Yap is a confirmed predictor of poor prognosis in a variety of cancers 34 including gastric cancer. 33 Moreover, the IHC image demonstrated a significant elevated nuclear location of Yap in GC tissues compared with noncancerous tissues, consistent with previous research. 35 Remarkably, we observed a decreased expression of Fat4 with concomitant increased nuclear location of Yap in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Both basic and clinical cancer research has implicated a role of YAP and TAZ in cancer initiation and development through suppressing cell apoptosis and promoting cell prolifieration (Moroishi et al 2015a). Concordantly, YAP and TAZ have been considered as therapeutic targets for a number of cancers (Liu-Chittenden et al 2012;Jiao et al 2014;Yu et al 2014;Zhou et al 2015b) as well as several other diseases . Notably, the R331W missense mutation of YAP has recently been linked to a germline risk in lung adenocarcinoma (Chen et al 2015a).…”
Section: The Yap/taz Transcriptional Programs and Their Functional Oumentioning
confidence: 99%
“…Several studies have suggested a potential link between YAP/TAZ signaling and gastric cancer (12)(13)(14)(15). YAP expression is upregulated in gastric tumor samples compared to normal tissue, and the total amount of YAP expression as well as its nuclear localization are significantly correlated with poorer clinical outcomes (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…YAP expression is upregulated in gastric tumor samples compared to normal tissue, and the total amount of YAP expression as well as its nuclear localization are significantly correlated with poorer clinical outcomes (12)(13)(14). Moreover, a peptide mimicking the role of VGLL4 (a candidate for inhibiting the YAP-TEAD interaction) inhibits tumor growth in both xenograft and carcinogen-induced murine gastric tumor models (15).…”
Section: Introductionmentioning
confidence: 99%